Potential Utilization of Palms as Weaving Tools and Crafts in the Acehnese Community in Gandapura District, Bireuen Regency - Cut Roswita; Syifa Saputra; Erlia Hanum; Tutiliana Tutiliana; Nadia Aldyza (Yayasan Adra Karima Hubbi, 2024)
Gandapura sub-district is an area that has the potential of unique natural resources rich in flora and fauna. However, the potential possessed by the community in processing palms has not been developed, and has not been able to increase market sales in order to improve the needs of their daily lives, In the end, this research activity was carried out can have an impact on community empowerment in increasing the production of plaits and community skills. already known information about the use of plants as tools, plaits and crafts by the community in this area, conducted an exploration of the existing knowledge in the community. The method used was participatory observation, questionnaires and semi-structured and free in-depth interviews (open ended) on various age groups, The results showed 7 types of plants for the production of tools, plaits and crafts, these types are Bak Jok ('), bak Pineng (Areca catechu), bak Teue (Borassus flabellifer), Ibus (carypha Utan) bak U (Cocos nucifera), bak Meria (Metroxylon sago), and bak Lipah (Nypa fruticans).